A Map of American Literature - Pascual Soler, Nieves (CD Innovación docente, 2013)
The aim of the contents included in this CD is to provide students with useful and motivating activities that help them improve their knowledge of American literature and culture. This publication is divided into two sections. Section One, titled "A Survery of american Literature," focuses on the main literary texts written in the United Stated since 1620 to the comtemporary period. Section Two, "American Modernisms", center on American Modernist Literature (1920-1939). A list of updated bibliographical references is offered. We hope students enjoy learning American Literature as much as we enjoy teaching it.